Is air pollution a potential cause of neuronal injury?. (3rd August 2019) - Ji, Yu; Stone, Christopher; Guan, Longfei; Peng, Changya; Han, Wei
ABSTRACT: Introduction : Fine particle pollution, including diesel exhaust particles (DEP), is a well-recognized and significant threat to public health. Cerebrovascular disease has been shown to be among the pathologies produced by fine particle exposure, and is thought to arise in this context through oxidative and inflammatory mechanisms. The manner by which these mechanisms interface with normal cerebral metabolism in their promotion of cerebrovascular pathogenesis, however, remains to be elucidated. Recent evidence has emerged that implicates a new pathway in post-stroke oxidative injury: gluconeogenesis. Therefore, we investigated whether diesel exhaust particle (DEP)-mediated oxidative injury to brain cells was associated with upregulation of the gluconeogenic pathway. Methods : Human neuroblastoma SH-SY5Y cells were maintained in complete Dulbecco's Modified Eagle's Medium (DMEM)/F12 at 37°C. Cells were exposed to freshly dispersed DEP preparations at 0, 6.25, 12.5, 25, 50, 100, or 200 µg/ml for either 3 or 24 h. Cell survival was then gauged by MTT assay, intracellular oxidative stress was quantified by fluorescence, and expression of gluconeogenic enzymes was assayed by quantitative RT-PCR. Results : Exposure to increasing concentrations of DEP yielded proportional, significant decreases in cell viability in conjunction with proportional, significant increases in intracellular ROS generation. These findings occurred in the context of DEP-induced reactive gluconeogenesis, as demonstrated by significant transcriptional upregulation of the key regulatory gluconeogenic enzymes PEPCK, PC, G6PC, and FBP. Conclusion : Gluconeogenesis was induced in human neural cells exposed to fine particles (DEP), in association with cell damage and oxidative stress. These findings suggest that the pathogenesis of cerebrovascular injury due to fine particle pollutant exposure may proceed through derangements in gluconeogenic metabolism. Abbreviations: DEP: diesel exhaust particles, ICA: intracranial atherosclerosis, ROS: reactive oxygen species